Association of high-sensitivity C-reactive protein and long-term mortality may differ from lipoprotein(a) levels among patients undergoing coronary angiography. (25th November 2020) - Guo, Z; Lei, L; Ying, M; Wang, B; Liu, J; Liu, L; He, Y; Sun, G; Chen, S; Liu, B; Chen, G; Chen, J; et al.
Abstract: Background: The use of high-sensitivity C-reactive protein (hs-CRP) as an inflammation biomarker in predicting long-term mortality remains controversial. We aimed to investigate whether the association of hs-CRP with long-term mortality differs from another inflammation biomarker, lipoprotein(a), in patients undergoing coronary angiography (CAG). Methods: A total of 2422 patients undergoing CAG were included in the final analysis from a prospective, observational study. We divided them into 4 groups according to hs-CRP level (high ≥4.8 mg/l, low <4.8 mg/l) and lipoprotein(a) level (high ≥17 mg/dl, low <17 mg/dl). Results: The overall incidence of all-cause long-term mortality was 133/2422 (5.5%). In the high lipoprotein(a) group, after adjusting for LDL-cholesterol concentration (LDL-C), age, sex, smoking status, diabetes mellitus and estimated glomerular filtration rate (eGFR), a high hs-CRP level was an independent predictor of all-cause long-term mortality (hazard ratio: 2.01; 95% CI: 1.13–3.54; p=0.02). In the low lipoprotein(a) group, a similar result was not found (hazard ratio: 1.42; 95% CI: 0.92–2.01; p=0.24). Conclusions: Our data suggested that the association of hs-CRP with all-cause long-term mortality may differ from lipoprotein(a) levels among patients undergoing CAG. In addition to hs-CRP, a high lipoprotein(a) level might be a simultaneous intervention target for improving long-term prognosis in the future. Funding Acknowledgement: Type of funding source: None